Development and Evaluation of the Content and Face Validity of an Mpox Questionnaire for Primary Healthcare Workers - Abdullah, Muhammad Saufi; Mohd Hairon, Suhaily; Mohd Yusoff, Siti Suhaila; Abdullah Zakaria, Mohd Azimullah; Mohd Nawi, Mohd Shamril (Malaysian Journal of Medical Sciences, 2026)
Background: Primary healthcare workers are essential in managing infectious diseases, including mpox. A validated instrument is required to assess their knowledge and readiness for mpox management. This study evaluated the content and face validity of a Malay-language mpox questionnaire for primary healthcare workers in Malaysia.Methods: Questionnaire development was conducted in two stages: i) item generation and ii) judgement and quantification. Ten experts from relevant disciplines assessed content validity, while 10 primary healthcare workers participated in face validation. The content validity index (CVI), face validity index (FVI), and modified Kappa were calculated to evaluate clarity, relevance, necessity, and representativeness.Results: The initial questionnaire comprised 62 items across two domains (knowledge and readiness). During content validation, one item assessing clarity yielded an item-level CVI (I-CVI) of 0.70 and a modified Kappa of 0.67; other items achieved excellent thresholds (I-CVI ≥ 0.78; modified Kappa ≥ 0.74). Scale-level CVI (S-CVI/Ave) across all criteria was >0.90, indicating excellent overall validity. The universal agreement S-CVI (S-CVI/UA) for relevance was 0.76, slightly below the recommended cut-off. Based on these findings and expert recommendations, one item was removed due to subthreshold performance and redundancy. Face validation demonstrated strong comprehensibility, with item-level FVI (I-FVI), scale-level FVI (S-FVI/Ave), and universal agreement S-FVI (S-FVI/UA) values exceeding recommended thresholds (0.78, 0.90, and 0.83, respectively). The final questionnaire contained 61 items.Conclusion: This study provides a validated Malay-language questionnaire for assessing knowledge and readiness for mpox management among primary healthcare workers. This tool provides a standardised approach for identifying knowledge gaps and guiding targeted training to strengthen outbreak preparedness.